2009
DOI: 10.1093/geront/gnp013
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Living Arrangements, and Social Circumstances as Determinants of Entry Into and Exit From Long-Term Institutional Care at Older Ages: A 6-Year Follow-Up Study of Older Finns

Abstract: Gender, age, living arrangements, and socioeconomic status are major determinants of institutional residence. Women and certain other population groups, e.g., those living alone, are likely to spend a longer time in institutional care because of higher rates of entry and lower rates of exit. These results have implications for the financing of long-term care and for targeting of interventions aimed at delaying it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
3
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 34 publications
4
63
3
9
Order By: Relevance
“…The protective effect of marriage is in line with findings in earlier studies (e.g. Nihtilä and Martikainen 2008;Martikainen et al 2009). Earlier research has not, to our knowledge, included the cohabiting as a separate category; little is known about their excess risk of entering an institution for the elderly.…”
Section: Data and Assumptionssupporting
confidence: 92%
See 1 more Smart Citation
“…The protective effect of marriage is in line with findings in earlier studies (e.g. Nihtilä and Martikainen 2008;Martikainen et al 2009). Earlier research has not, to our knowledge, included the cohabiting as a separate category; little is known about their excess risk of entering an institution for the elderly.…”
Section: Data and Assumptionssupporting
confidence: 92%
“…This means that persons in an institution with a partner who lives elsewhere have more fragile health than persons who do not have a partner. In support of this idea, Martikainen et al (2009) found that those living alone were in better health when moving to an institution than those living with a spouse or cohabiting. Source: Own computations based on data supplied by Statistics Finland.…”
Section: Data and Assumptionsmentioning
confidence: 94%
“…Apabila warga emas tinggal di institusi, sama ada yang masih mempunyai anak atau tidak, secara tidak langsung mereka telah terputus hubungan dengan komuniti asal dan juga anak-anak atau waris. Tiada lagi sokongan yang diterima daripada ahli keluarga, anak-anak atau waris dari segi emosi dan bantuan tertentu (Martikainen et al 2009). Warga emas yang berada di dalam komuniti pula mempunyai gambaran yang negatif terhadap kehidupan di dalam institusi.…”
Section: Pengenalanunclassified
“…Peningkatan keperluan perkhidmatan penjagaan sama ada penjagaan tidak formal oleh ahli keluarga ataupun penjagaan formal di institusi adalah kesan daripada peningkatan populasi warga emas. Berbanding dengan penjagaan tidak formal, penjagaan formal di institusi adalah pilihan terakhir bagi warga emas dan merupakan suatu pilihan yang tidak popular serta dibuat bukan dengan kerelaan hati (Martikainen et al 2009). …”
Section: Pengenalanunclassified
“…Within this category of papers we can identify two distinct categories -those which aim to relate aggregate demand and cost of LTC with socioeconomic variables and those which aim to understand the type and or level of LTC consumed by an individual patient. In the case of the former class of papers, such factors include: prevalence rates of disease (Macdonald & Cooper, 2007); rates of mortality (Comas-Herrera, Whittenberg, Pickard, & Knapp, 2007); cultural attitudes towards care of the elderly (Kim & Kim, 2004); future patterns of care and general improvements in the level of health (Karlsson M. , Mayhew, Plumb, & Rickayzen, 2006); and living status (Martikainen, et al, 2009). In the latter class of papers, factors identified include: proximity to death (Murphy & Martikainen, 2010) (Weaver, Stearns, Norton, & Spector, 2009) (De Meijer C. , Koopmanschap, Bago D'Uva, & Van Doorslaer, 2011); type and no of diagnoses (Huang, Lin, & Li, 2008); level of disability (De Meijer C. A., Koopmanschap, Koolman, & Van Doorslaer, 2009) (Imai & Fushimi, 2011); and marital status (Woo, Ho, Yu, & Lau, 2000) (Wong, Elderkamp-de Groot, Polder, & Van Exel, 2010).…”
Section: Modelling the Demand For Ltcmentioning
confidence: 99%